Synthesis and antitumor activity of certain 2,3,6-trisubstituted quinazolin-4(3H)-one derivatives - Safinaz E. Abbas; Flora F. Barsoum; Hanan H. Georgey; Eman R. Mohammed (Bulletin of Faculty of Pharmacy Cairo University, 2013)
The synthesis of different series of 6-iodo-2-phenoxymethyl 3-substituted quinazolin-4(3H)-ones 5–17 is described. The structures of the newly synthesized compounds have been confirmed on the basis of elemental analyses, IR, 1H NMR and mass spectral data. Preliminary testing for the in vitro antitumor activity of the synthesized compounds against MCF-7 breast cell line was carried out using Doxorubicin (IC50: 5.46 μmol/ml) as a reference drug. Compound 5b exhibited a remarkable antitumor activity (IC50: 5.49 μmol/ml) almost similar to that expressed by the reference drug, whereas compounds 7d, 12b and 6c (IC50: 6.23, 6.55 and 6.80 μmol/ml, respectively) showed a considerable activity.